Knowing What Works: Creating Circles of Courage - Van Bockern, Steve; Brendtro, Larry K.; Brokenleg, Martin (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2022)
Early attempts to help children experiencing academic or behavorial problems were based on an eclectic mix of inconsistent and sometimes harsh and punitive strategies. Drawing from Indigenous cultures, the Circle of Courage embodies four key growth needs that are essential to human wellbeing in any culture: Belonging, Mastery, Independence, and Generosity. This paper analyzes some of the diverse interventions that would support these four components.